1989
DOI: 10.1038/337184a0
|View full text |Cite
|
Sign up to set email alerts
|

An Fc receptor structurally related to MHC class I antigens

Abstract: Maternal immunoglobulin G transmitted to the fetus or newborn provides humoral immunity for the first weeks of mammalian life. Fc receptors on intestinal epithelial cells of the neonatal rat (FcRn) mediate the uptake of IgG from milk. Affinity-purified FcRn is resolved by SDS-PAGE into components of relative molecular masses 45,000-53,000 (p51) and about 14,000 (p14). We report the identification of the smaller component as beta 2-microglobulin. Association of beta 2-microglobulin with p51 was confirmed by cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
483
0
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(496 citation statements)
references
References 29 publications
5
483
0
8
Order By: Relevance
“…The NCBI protein accession numbers are: NM_004107 (human) [24], CAH91593 (orangutan), AF485818 (macaque), AF421499 (sheep) [25], AF221522 (cattle), NP_999362 (pig) [26], AY894681 (camel) [27], XM_533618 (dog), NM NM_033351 (rat) [28], Q61559 (mouse) [29] and AF191647 (possum) [30]. Fig.…”
Section: Fcrn Sequence Analysismentioning
confidence: 99%
“…The NCBI protein accession numbers are: NM_004107 (human) [24], CAH91593 (orangutan), AF485818 (macaque), AF421499 (sheep) [25], AF221522 (cattle), NP_999362 (pig) [26], AY894681 (camel) [27], XM_533618 (dog), NM NM_033351 (rat) [28], Q61559 (mouse) [29] and AF191647 (possum) [30]. Fig.…”
Section: Fcrn Sequence Analysismentioning
confidence: 99%
“…4,8,9 A pivotal molecule responsible for the transfer of maternal IgG is neonatal Fc receptor (FcRn), which was first identified in the small intestine of neonatal rats where it mediates uptake of IgG from milk. 10 FcRn is a major histocompatibility complex class I related molecule consisting of an a-chain and b2-microglobulin and its major roles are to protect both IgG and albumin from catabolism and so extend their half-lives 3,11,12 in addition to transporting IgG through multiple mucosal barriers.…”
Section: Introductionmentioning
confidence: 99%
“…This prolonged half-life of IgG can be explained by the interaction with neonatal FcR (FcRn). FcRn is a heterodimer of the MHC class I-like H chain and the b 2 -microglobulin (b 2 m) L chain (2). Although this receptor was originally studied as a transporter of IgG from mother to fetus, subsequent studies have shown that this receptor also plays a critical role in regulating IgG homeostasis (3,4).…”
mentioning
confidence: 99%